How can we better manage drug‐resistant OAB/DO? ICI‐RS 2018. (10th December 2019) - Chermansky, Christopher; Schurch, Brigitte; Rahnama'i, Mohammad S.; Averbeck, Marcio A.; Malde, Sachin; Mancini, Vito; Valentini, Francoise; Sahai, Arun
Abstract: Aims: Botulinum toxin A (BTX‐A), sacral nerve stimulation (SNM), and posterior tibial nerve stimulation (PTNS) are established treatments for idiopathic overactive bladder (OAB) refractory to oral drug therapy. At the ICI‐RS meeting in Bristol in 2018 a think tank was convened to address the question of how to better manage drug‐resistant OAB/DO (detrusor overactivity). Methods: The think tank conducted a literature review and an expert consensus meeting focusing on the evidence for predicting response and adverse events (AEs) with the current therapies for drug‐resistant idiopathic OAB. Results: Several factors have been associated with poor outcomes using BTX‐A including increasing age, body mass index, male sex, and frailty. Voiding dysfunction with BTX‐A also appears to be more prevalent in those with increasing age, male sex, higher baseline postvoid residual and with poorer contractility as assessed by urodynamic parameters. SNM full implantation appears to be higher with the first stage tined lead placement procedure compared to percutaneous nerve evaluation. Urodynamics do not appear to predict outcomes with SNM. Patients with psychiatric comorbidity are more likely to experience AEs with SNM. Outcomes related to lead positioning and the number of active electrodes are mixed in predicting long term success. Patients with increased daytime frequency and lower first sensation of bladder filling were independent factors associated with success with PTNS. Conclusions: Further research is required to optimize these procedures and to better understand which patients will benefit from the various options available in managing refractory OAB.